1977
DOI: 10.3758/bf03214479
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a continuing computer conference on simulation

Abstract: A 20-day computer conference was held in preparation for a face-to-face meeting to produce a computer simulation. The conferencing resulted in the generation of seven different models and was excellent preparation for the subsequent meeting. Computer conferencing appears to hold great value for faculty development in a period of reduced faculty mobility.Sedelow (I976) has pointed out that a computer network has a multitude of elements, and a thorough description and evaluation of the entire person-machine syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…RELATED LITERATURE CMCS may facilitate the improvement in the information processing systems of organizations. For example, CMCS has been related to a more efficient flow of information up, down, and across organizations (Furgeson, 1977 ;Katzman, 1974;Pool, 1983; Rice & Bair, 1984;Rogers, 1986;Spelt, 1977;Strassman, 1985); to greater access to information and individuals (both local and remote); and to creating greater access to organizational power, decision making, and creative processes (Gengle, 1984;Kiesler, Siegel, & McGuire, 1984;Rice 1980). Also CMCS has been linked to increases in the amount of information distributed and consumed (Ito, 1981;Pool, 1983;Rogers, 1986); concerns about information overload (Rogers, 1986); increased separation between information poor and rich (Katzman, 1974;Pool, 1983); alterations in organizational structure (Allen & Hauptman, 1987); increased communication activities within functional groups and in superior-subordinate relationships (Rice, 1980); more effective communication with external environments (Rice, 1987); more open organizational networks (Rice, 1987); and a decrease in the amount of face-to-face and telephone communication (Kaye & Byrne, 1986;Sumner, 1985).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…RELATED LITERATURE CMCS may facilitate the improvement in the information processing systems of organizations. For example, CMCS has been related to a more efficient flow of information up, down, and across organizations (Furgeson, 1977 ;Katzman, 1974;Pool, 1983; Rice & Bair, 1984;Rogers, 1986;Spelt, 1977;Strassman, 1985); to greater access to information and individuals (both local and remote); and to creating greater access to organizational power, decision making, and creative processes (Gengle, 1984;Kiesler, Siegel, & McGuire, 1984;Rice 1980). Also CMCS has been linked to increases in the amount of information distributed and consumed (Ito, 1981;Pool, 1983;Rogers, 1986); concerns about information overload (Rogers, 1986); increased separation between information poor and rich (Katzman, 1974;Pool, 1983); alterations in organizational structure (Allen & Hauptman, 1987); increased communication activities within functional groups and in superior-subordinate relationships (Rice, 1980); more effective communication with external environments (Rice, 1987); more open organizational networks (Rice, 1987); and a decrease in the amount of face-to-face and telephone communication (Kaye & Byrne, 1986;Sumner, 1985).…”
mentioning
confidence: 99%
“…Due to the low level of social presence when using CMCS compared with other forms of interaction, users have less ability to communicate status and hierarchy in social relationships (Kiesler et al, 1984;Short, Williams, & Christie, 1976). In comparison to face-to-face communication, CMCS has been reported to be more concise, logical, direct, organized, careful, functional, serious, businesslike, depersonalized, task-oriented, and less emotional, friendly, informal, personal, relaxed, and spontaneous (Furgeson, 1977;Hiemstra, 1982;Johansen & DeGrasse, 1979;Krueger & Champanis, 1980;Spelt, 1977). Researchers have found that users learn to substitute written cues for nonverbal cues that may be essential to developing and maintaining social relationships (Hiltz, Turoff, & Johnson 1985;Love & Rice,1985;Phillips,1983;Pollack,1982;Rafaeli,1983;Spelt,1977).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen years ago, Walter Sedelow (Sedelow, 1976) outlined how networks would change the way we work. In the next year, Phil Spelt and Karl Zinn (Spelt, 1977;Zinn, 1977) presented what then were state-of-theart techniques for computer conferencing. What they described is not much different from what we can now accomplish easily with BITNET or INTERNET, but I think that all three underestimated the extent to which we would depend on electronic communications and data highways in the 199Os.…”
mentioning
confidence: 99%
“…physically separated and through a computer, many researchers have investigated the effects on the social-emotional content of interpersonal messages. Some researchers blamed the narrow bandwidth of computer networking for an increase in the seriousness, depersonalized, businesslike, and task oriented nature of interaction and a decrease in emotional and friendly elements (Furgeson, 1977;Hiemstra, 1982;Hiltz & Turoff, 1978;Johansen & DeGrasse, 1979;Krueger & Chapanis, 1980;Lin, 1987;Rogers, 1986;Spelt, 1977;Vallee, Johansen, Lipinski, Spangler, Wilson, & Hardy, 1975;Vallee et al, 1978). Rogers found that 30% of interactions made via an electronic bulletin board dealt with socio-emotional content.…”
Section: Because Computer Networking Communication Occurs Between Intmentioning
confidence: 99%